PENDIDIKAN KEWIRAUSAHAAN MASA COVID-19 : SATU TINJAUAN - Nazaruddin Ali Basyah; Irham Fahmi; A. Razak (PENCERAHAN, 2020)
Entrepreneurship is the cause and consequence of economic growth, technological progress,as well as conceptual innovation, which are are interrelated, interconnected and interwoven. Searching for individuals that are willing to share their knowledge and expertise shouldbe in line with a comprehensive and effective learning strategy that meets up with the demand of the market and government. This study aims to develop the skills and knowledge of Acehnese students that are willing to make entrepreneurship their career. Furthermore, it brings scholars closer to education, entrepreneurial culture, and business opportunities, as well as the latest business management science. The study of the importance of entrepreneurship education is also part of the entrepreneurship culture and practice of values of professionalism and higher ethics. The entrepreneurship education index had a negative impact on staying at home during Covid-19.